2021
DOI: 10.3390/ijms222212494
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and Pathological Cell Interactions: Mitochondrial Glucose Processing in Cancer Cells

Abstract: Melatonin is synthesized in the pineal gland at night. Since melatonin is produced in the mitochondria of all other cells in a non-circadian manner, the amount synthesized by the pineal gland is less than 5% of the total. Melatonin produced in mitochondria influences glucose metabolism in all cells. Many pathological cells adopt aerobic glycolysis (Warburg effect) in which pyruvate is excluded from the mitochondria and remains in the cytosol where it is metabolized to lactate. The entrance of pyruvate into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 243 publications
(324 reference statements)
0
25
0
Order By: Relevance
“…Melatonin is a direct ROS scavenger ( 1 O 2 , O 2 • − ,•OH) by donating electron(s) to the ROS, with the formation of products such as cyclic 3-hydroxymelatonin or indolyl radical cation of low reactivity [ 123 ]. Melatonin can be also supplied exogenously from diet or supplements [ 125 ] to heal jet lag, insomnia, narcolepsy and other sleep disorders, and is considered as a potential cardioprotective, anti-inflammatory and anti-cancer agent [ 126 ].…”
Section: Anti-oxidant Mechanisms As a Protection Against Oxidative-st...mentioning
confidence: 99%
“…Melatonin is a direct ROS scavenger ( 1 O 2 , O 2 • − ,•OH) by donating electron(s) to the ROS, with the formation of products such as cyclic 3-hydroxymelatonin or indolyl radical cation of low reactivity [ 123 ]. Melatonin can be also supplied exogenously from diet or supplements [ 125 ] to heal jet lag, insomnia, narcolepsy and other sleep disorders, and is considered as a potential cardioprotective, anti-inflammatory and anti-cancer agent [ 126 ].…”
Section: Anti-oxidant Mechanisms As a Protection Against Oxidative-st...mentioning
confidence: 99%
“…During SARS-CoV-2 infection, viral ORF3a induces HIF-1α activation, which in turn aggravates viral infection and inflammatory responses ( 275 ). Melatonin may attenuate the damage resulting from COVID-19-mediated septicemia by mollifying HIF-1α, suppressing NF-κB, inhibiting the inflammasome, converting pro-inflammatory M1 macrophages to anti-inflammatory M2 macrophages, and reversing Warburg-type metabolism ( 276 278 ). After administration as an adjuvant therapy, melatonin was found to attenuate Th1 and Th2 inflammatory cytokines by downregulating the expression of Th1 and Th2 regulatory genes in patients with COVID-19 ( 279 ).…”
Section: Potential Adverse Effects Of Melatonin In the Elderlymentioning
confidence: 99%
“…Some antitumor characteristics of melatonin are dependent on activation of the MT1 receptor; however, melatonin also exerts intracellular effects that are independent of MT1 [ 4 ]. Previous studies demonstrated that melatonin reaches specific subcellular compartments through the glucose transporter (GLUT1) and human peptide transporter 1 and 2 (PEPT1/2) [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria are the organelles responsible for cell metabolic functions such as energy production, pyruvate metabolism, and cellular respiration (oxidative phosphorylation or OXPHOS) [ 15 , 20 ]. Metabolic reprogramming that induces high glycolytic rates even in the presence of oxygen (Warburg effect) is a hallmark of cancer [ 4 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation